Digital government in the archipiélago of San Andrés, providencia and Santa Catalina (2021)
This essay aims to show the reality facing the public administration in the archipelago of San Andrés, Providence and Santa Catalina to advance in the implementation of digital government, seeking to discuss its importance in the governance of the territory. This essay is a documentary, historical-chronological type investigation that implements an analytical method, which conceives findings for the implementation of digital government in the archipelago of San Andrés, Providence and Santa Catalina, showing problems in the areas: Technical, social , economic and political, concluding that there is a very strong contrast between what should be and what it is, showing a high degree of shortcomings within the local public administration, jointly with the national government.